2015
DOI: 10.1155/2015/478753
|View full text |Cite
|
Sign up to set email alerts
|

TACI Expression and Signaling in Chronic Lymphocytic Leukemia

Abstract: TACI is a membrane receptor of BAFF and APRIL, contributing to the differentiation and survival of normal B cells. Although malignant B cells are also subjected on TACI signaling, there is a remarkable intradisease and interindividual variability of TACI expression in B-cell malignancies. The aim of our study was to explore the possible role of TACI signaling in the biology of chronic lymphocytic leukemia (CLL), including its phenotypic and clinical characteristics and prognosis. Ninety-four patients and 19 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
4
10
0
Order By: Relevance
“…There are several studies which investigate the prognostic role of these molecules in hematological malignancies, particularly in CLL. In a study by Mamara et al [28], BAFF and TACI levels were found to be lower in 94 CLL patients, however a significant association with clinical or laboratory risk factors was not demonstrated in concordance with our results. Similar results were reported in two studies by Planelles et al and Haiat et al [30,31].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…There are several studies which investigate the prognostic role of these molecules in hematological malignancies, particularly in CLL. In a study by Mamara et al [28], BAFF and TACI levels were found to be lower in 94 CLL patients, however a significant association with clinical or laboratory risk factors was not demonstrated in concordance with our results. Similar results were reported in two studies by Planelles et al and Haiat et al [30,31].…”
Section: Discussionsupporting
confidence: 65%
“…In order to highlight the pathophysiological role of this complicated biological network, we aimed to analyze the potential prognostic effects of BAFF, APRIL, TACI and BCMA in CLL patients [16,18,[28][29][30][31][32][33][34][35][36]. Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicated that high TACI expression improves the survival ability of CLL cells by protecting them from apoptosis in vitro [ 18 , 19 ], which in consequence may worsen the clinical course of the disease. Therefore, we decided to make additional analysis, and check whether we will be able to notice relationship between high TACI expression and Rai stage (Rai Staging System).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the APRIL-TACI interaction has been shown to be pivotal to a class switch recombination (CSR) to IgA [ 11 ]. Additionally, some studies indicated that a high TACI expression improves the survival ability of CLL cells protecting them from apoptosis in vitro [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…cDNA was prepared from total RNA from mononuclear cells as described (26, 27). Expression of TACI and BAFFR was determined by quantitative Real-Time RT-PCR, while the expression of BCMA, APRIL, BAFF , and deltaBAFF (Δ BAFF ) transcripts was determined by semi-quantitative conventional RT-PCR using beta-2-microglobulin (B2M) transcripts as reference (Supplementary Methods).…”
Section: Methodsmentioning
confidence: 99%